Pengelolaan Zakat Oleh Negara-Badan Amil Zakat (BAZ) (Studi Terhadap Sikap Muzakki di Kota Bengkulu) - Asnaini, Asnaini (Institut Agama Islam Bengkulu, 2017)
Attitudes are important and often affect a person's behavior. Therefore understanding one's attitude can help understand and predict their behavior in everyday life. This study aims to analyze the attitude of muzakki towards the management of zakat by the BAZNAS. This is because knowing the attitude of muzakki in paying zakat is very important to make efforts so that the community will increasingly care for BAZ and want to use it in distributing their zakat. Based on the results of the study using proportion tests showed that the majority of muzakki in Bengkulu City were negative towards the management of zakat by the Baznas.